Demographic Determinants and Adoption Patterns of Online Reputation Management Strategies among Marketing Professionals in India - Mishra , Ananya (Journal of Neonatal Surgery, 2025)
India on the adoption of online reputation management strategies to understand the dynamics of reputation in a changing and fast-evolving digital and technological world. Design/Methodology/Approach: The present study used a quantitative approach by collecting 150 marketing professionals as respondents from India. To examine the impact of demographic determinants such as age, gender, professional experience, and size of the organization on the selection of strategies of online reputation management, the statistical tools applied in the present study are ANOVA, Independent t-test, and Multivariate analysis. Findings: The findings of the study show that marketing practitioners limit the practical use of unethical strategies as they believe this will impact consumer trust and credibility more dangerously. Experienced and male professionals working in large firms have shown an easy adoption of technology-driven strategies such as SEO, which is supported by the theoretical theory TAM (Technology Acceptance Model). Gender-based differences and larger firms prioritize the Reputation Marketing proactive strategy, which requires strategic planning and investment to manage online reputation before any crisis occurs. Originality/Value: Previous studies mainly focus on corporate reputation, crisis communication, or consumer-level factors. This study aims to provide a valuable contribution of individual traits in decision-making for building and maintaining the reputation of an organization. This will help marketing organizations, academia, and practitioners who aim to strengthen their digital reputation management practices through training and development of such systems...